Bacteroidetes and Firmicutes Drive Differing Microbial Diversity and Community Composition Among Micro-Environments in the Bovine Rumen - Pinnell, Lee J.; Reyes, Arquimides A.; Wolfe, Cory A.; Weinroth, Maggie D.; Metcalf, Jessica L.; Delmore, Robert J.; Belk, Keith E.; Morley, Paul S.; Engle, Terry E. (Frontiers in Veterinary Science, 2022)
Ruminants are a critical human food source and have been implicated as a potentially important source of global methane emissions. Because of their unique digestive physiology, ruminants rely upon a symbiotic relationship with the complex and rich community of microorganism in the foregut to allow digestion of complex carbohydrates. This study used 16S rRNA gene sequencing to investigate the composition of microbial communities from three rumen micro-environments of cattle fed identical diets: 1) free fluid, 2) the fibrous pack, and 3) the mucosa. Community composition analysis revealed that while a phylogenetic core including the most abundant and most common ruminal taxa (members of Bacteroidetes and Firmicutes) existed across micro-environments, the abundances of these taxa differed significantly between fluid- and mucosa-associated communities, and specific lineages were discriminant of individual micro-environments. Members of Firmicutes, specifically Clostridiales, Lachnospiraceae, Mogibacteriaceae, Christenellaceae, and Erysipelotrichaceae were significantly more abundant in fluid communities, while members of Bacteroidetes, namely Muribaculaceae and Prevotellaceae were more abundant in mucosa-associated communities. Additionally, Methanobacteriaceae, a family of methanogenic Archaea, was more abundant in fluid-associated communities. A set of four more diverse lineages were discriminant of pack-associated communities that included Succinivibrionaceae, RFP12 (Verruco-5), Fibrobacteraceae, and Spirochaetaceae. Our findings indicate that different ecological niches within each micro-environment have resulted in significantly different microbial communities and provide baseline values for the diversity and community structure of microbial communities from rumen fluid, pack, and mucosa that can contextualize the influence of environmental factors such as diet.